Dementia prevalence, care arrangement, and access to care in Lebanon: A pilot study. Issue 12 (1st June 2017) - Phung, Kieu T.T.; Chaaya, Monique; Prince, Martin; Atweh, Samir; El Asmar, Khalil; Karam, Georges; Khoury, Rose Mary; Ghandour, Lilian; Ghusn, Husam; Nielsen, T. Rune; Waldemar, Gunhild
Abstract: Introduction: In North Africa and the Middle East, studies about dementia prevalence are scarce. A pilot study was conducted in Lebanon to assess dementia prevalence, using the Arabic‐validated 10/66 Dementia Research Group (DRG) diagnostic assessment for case ascertainment. The study also examined care arrangement and access to care. Methods: A random sample of 502 persons older than 65 years and their informant were recruited from Beirut and Mount Lebanon governorates through multistage cluster sampling. Results: The crude and age‐standardized dementia prevalences were 7.4% and 9.0%, respectively. People with dementia were mainly cared for by relatives at home. Access to formal care was very limited. Discussion: Dementia prevalence in Lebanon ranks high within the global range of estimates. These first evidence‐based data about disease burden and barriers to care serve to raise awareness and call for social and health care reform to tackle the dementia epidemic in Lebanon and in North Africa and the Middle East. Highlights: The crude dementia prevalence in Lebanon is 7.4%, whereas age‐standardized dementia prevalence is 9.0%. Age‐specific prevalences are 3.6 % for the age group 65 to 69 years, 4.8% for 70 to 74 years, 6.7% for 75 to 79 years, 19.0% for 80 to 84 years, and 20.6% for ≥85 years. The absolute number and the age distribution of dementia prevalence are consistent with the latest estimates for North Africa and the Middle East region from the World Alzheimer Report 2015. The burden of caregiving rests mainly with the family and access to dementia care is very limited. The findings provide the first evidence‐based data to raise awareness and advocate for sociomedico policy reform in the country.